PERANCANGAN SISTEM INFORMASI PADA PENJUALAN HIJAB TOKO KHANZANAH WIN BERKAH - Wahyu Indrarti; Rani Rani; Reni Widiastuti; Faisal Roni (JIPETIK:Jurnal Ilmiah Penelitian Teknologi Informasi & Komputer, 2021)
Abstract :In this era globalization, information technology is one of the fields whose development is accelerating. Information technology gives a lot of influence in the  life of the people and computers become the most sophisticated alternative in handling the right and accurate information . Khanzanah Win Berkah is a trading business engaged in fashion that the system is still manual and has not been computerized starting from recording data items, the sales transaction process to making report so as to make the store's performance less effective and efficient . Therefore, there needs to be a system that can facilitate employees in doing their jobs. For this reason, the author tries to make a Final Project on the design of sales information systems at KhanzanahWin Berkah. And the model used to design this software uses the waterfall model. The design of this information system is the best solution to solve existing problems in the shop and with a computerized system that can improve shop performance more effectively and efficiently so the data stored is save and reduces errors in data calculation.